2023
DOI: 10.1186/s12906-023-03842-y
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Chinese herbal medicine Guizhi Fuling capsule combined with low dose mifepristone in the treatment of uterine fibroids: a systematic review and meta-analysis of 28 randomized controlled trials

Abstract: Objective Guizhi Fuling Capsule (GZFL), a classic traditional Chinese medicine prescription, is often recommended for the treatment of uterine fibroids (UFs). However, the efficacy and safety of GZFL in combination with low-dose mifepristone (MFP) remains controversial. Materials and methods We searched eight literature databases and two clinical trial registries for randomized controlled trials (RCTs) of the efficacy and safety of GZFL combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A recent meta-analysis suggested the potential superiority of combined therapy involving mifepristone and Guizhi Fuling capsules, compared with mifepristone alone. However, authors emphasized the low quality of available data and underscored the need for high-quality randomized trials to prove initial findings [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis suggested the potential superiority of combined therapy involving mifepristone and Guizhi Fuling capsules, compared with mifepristone alone. However, authors emphasized the low quality of available data and underscored the need for high-quality randomized trials to prove initial findings [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alternative therapies, such as Chinese herbal preparations, phytochemicals, and novel drug delivery systems, show promising initial results. However, the majority of studies identified in this scoping review were conducted in an in vitro or ex vivo setting [44][45][46][47][48][49][50]. Randomized studies involving large cohorts of patients are necessary to assess the safety, efficacy, and clinical utility of potential new therapies.…”
Section: Discussionmentioning
confidence: 99%